Photoabsorption and photoconductivity in C₆₀ layers - Kanev, St.; Nenova, Z.; Koprinarov, N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
A complex investigation of the photoconductivity of fullerene films, prepared by thermal evaporation in vacuum, was carried out. The investigated films contain predominantly C₆₀ in various phases as shown elsewhere. The multiple photocurrent spectra analysis (MPSA method) has been used in the current study. The MPSA method utilizes a family of routine photocurrent spectra, measured at various intensities generated by the light source. A suitable data processing of such a family allowed several basic characteristics of the films to be obtained – the optical bandgap, subbandgap optical absorption spectra, features of shallow and deep defect states as well as the spectra of the power index in the dependence of the photocurrent on the photon flux. These characteristics were interpreted in terms of structural features of the investigated samples. Conclusions about applications of such C₆₀ films were made.